MEMPERKUAT PEMASARAN PENJUALAN PRODUK UMKM MELALUI PEMANFAATAN MEDIA SOSIAL: Studi di Desa Curug Sulanjana Kabupaten Serang - Rizqi Fitrianti; Achmad Nashrudin Priatna; Gusti Hidayatulloh (STAI Darul Qalam Tangerang, 2022)
The MSME seminar for MSME actors in Curug Sulanjana Village was based on the problem of the lack of use of social media as a product marketing strategy. The implementation of the MSME Seminar is a synergy between Bina Bangsa University students in the Student Work Lecture (KKM) Group 47, Community Service Lecturer Team (PkM), village officials and marketing consultants for MSME products which were attended by 12 groups of MSMEs for culinary products and 1 group of MSMEs. handicraft products in Curug Sulanjana Village. The activity was carried out in 1 meeting with a duration of 5 hours. This service concludes that social media plays an important role in strengthening the marketing strategy of MSME products in Curug Sulanjana Village, especially during the Covid-19 pandemic which is all-limited and all-digital. The use of social media has proven to be an effective supporting tool for MSME businesses during the Covid-19 pandemic, with a note that creativity is still needed for packaging messages in product promotions. Therefore, it is important for MSMEs to understand and add insight into digital marketing strategies